ELUCIDATION OF THE INDUCED CHIRALITY OF DANSYLGLYCINE BY ITS INTERACTION WITH HUMAN SERUM ALBUMIN - Souza, Aguinaldo Robinson de [UNESP]; Ferreira Boza, Izahelle Amorim [UNESP]; Ximenes, Yaldecir Farias [UNESP]; Yoguin, Mauricio Ikeda [UNESP]; Davila-Rodriguez, Maria-Jose; Morgon, Nelson Henrique; Caracelli, Ignez (Soc Brasileira Quimica, 2019)
Human serum albumin (HSA) plays an important role in the transport of a wide variety of substances, including compounds with pharmacological properties. The dansylglycine (DanG) is a fluorescent amino acid derivative specific for the site II of HSA. This work aimed to elucidate the induction of chirality in the DanG due to its bonding to the HSA. Theoretical electronic circular dichroism spectra (ECDs) were simulated using the Density Functional Theory (DFT) and the implicit Solvation Model based on Density (SMD). The DanG-HSA complexation resulted in the appearance of a positive ECD spectrum centered at 346 nm. Focusing on the dihedral angles between the - N(CH3)(2) group bounded to the naphthalene ring, the potential energy surface (PES) of the DanG was obtained. Analysis of the various conformations obtained revealed that the calculated dihedral angle (150 degrees) is in agreed with the experimental ECD spectrum. In addition, we observed that the nitrogen atom of the - N(CH3)(2) group presented the greatest contribution to the HOMO-LUMO transition that gives rise to the n ->pi* electronic transition involved in the generation of the ECD signal. Molecular docking analysis of the complexation between DanG and HSA revealed a conformation with a dihedral angle similar to that obtained by DFT.
Keywords: human serum albumin; DFT; electronic circular dichroism; dansylglycine